Responses of Plant Biomass in the Brazilian Savanna to Frequent Fires - Gomes, Letícia; Miranda, Heloisa Sinátora; Soares-Filho, Britaldo; Rodrigues, Lucas; Oliveira, Ubirajara; Bustamante, Mercedes M. C. (Frontiers in Forests and Global Change, 2020)
Fire has been a natural feature of the ecosystems for million years. Still, currently fire regimes have been increasingly altered by human activities and climate change, causing economic losses, air pollution, and environmental damage. In Brazil, savannas (locally known Cerrado) occupy almost 25% of the country´s area and concentrate 70% of burned area. Fire frequency is related to the use of biannual fire in agricultural practices, aiming at cleaning of cattle pasture, which act as ignition sources for the surrounding natural vegetation. Here, we present an ecological model to demonstrate how biennial fire affect plant biomass and carbon release from fine fuel in the Cerrado. The model BEFIRE (Behavior and Effect of Fire) is the first quantitative model that simulates the relationships between fire frequency, plant biomass, and fire-associated emissions based on the synthesis of knowledge about fire behavior and effects on ecosystems compiled from experimental burnings in the Cerrado. Our model uses microclimate variables and vegetation structure (the amount of aboveground biomass of trees, shrubs, herbs, and grasses) as inputs, and generates outputs related to the fire behavior (fire spread rate, fire intensity, and heat released) and the fire effects on the dynamic of plants biomass and post-fire carbon emission. The BEFIRE model predicts that biennial fires allow the recovery of the biomass of herbs and grasses’ biomass, due to its fast growth. However, this fire interval does not allow recovery of the biomass of shrubs and trees’ biomass. These growth limitations alter the co-existence of trees/shrubs and herbs/grasses and prevent the uptake of total amount of emitted carbon from combustion of fine fuel. Based on the model results, we proposed some recommendations for the fire management in this threatened biome.